2002
DOI: 10.1021/jp0124490
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Coherence Due to Promoting Mode Activity in the Relaxation Dynamics of the Class III Mixed-Valence Molecule [Ru2TIEDCl4]+

Abstract: We present the first measurements of the excited-state relaxation dynamics of a bimetallic class III mixedvalence molecule. The 800 nm absorption of [Ru 2 TIEDCl 4 ] + (TIED ) tetraiminoethylenedimacrocycle) relaxes in 250 and 1000 fs to at least two different intermediate states that can be followed with transient absorption spectroscopy. These states decay in 1.3 and 11.5 ps, and the absorption of the 1.3 ps intermediate displays a large amplitude, very low frequency, highly damped vibrational coherence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 103 publications
1
29
0
2
Order By: Relevance
“…Conventional molecular bridges contain donor atoms for metal binding in a bis-monodentate (1), [10][11][12] bis-bidentate (11), [53][54][55] bis-tridentate (12), [56][57][58][59] or bis-tetradentate [60] fashion (13), connected to a "spacer" which typically ensures p conjugation and determines the metal-metal distance.…”
Section: Beyond "Spacers": Structurally Sophisticated Bridging Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional molecular bridges contain donor atoms for metal binding in a bis-monodentate (1), [10][11][12] bis-bidentate (11), [53][54][55] bis-tridentate (12), [56][57][58][59] or bis-tetradentate [60] fashion (13), connected to a "spacer" which typically ensures p conjugation and determines the metal-metal distance.…”
Section: Beyond "Spacers": Structurally Sophisticated Bridging Ligandsmentioning
confidence: 99%
“…[27] However, the use of increasingly variegated bridging ligands, especially with chelate functions of variable denticity (bis-bidentate, bistridentate, or bis-tetradentate ligands) [55][56][57][58][59][60] has shown that these two manifestations of metal-metal interaction may not run in parallel but can be very different in magnitude. [98] In comparison to the Creutz-Taube ion as a standard, Table 5 illustrates cases with small K c values and intense IVCT bands (bis-tridentate acceptor bridges) [56][57][58] as well as examples with very large K c values but weak or non-observable IVCT features, typically exhibited by diruthenium(III,II) compounds with tris-or bis-bidentate acceptor bridges.…”
Section: Independence Of Electrochemical and Spectroscopic "Coupling"mentioning
confidence: 99%
“…Such a system was first introduced by Horiuti and Polanyi in 1935 to describe proton and hydrogen transfer reactions 1 and was subsequently extended by Hush to oxidation-reduction processes 2 in 1953, now forming the basis of modern electron-transfer theory [3][4][5][6] describing for example exciton and charge transport through molecules, organic conductors and organic photovoltaics as well as electron-transfer reactions in biochemistry. [7][8][9][10][11][12][13][14][15][16][17][18] It also describes general racemization processes 19,20 and has been widely used in spectroscopic analyses, [21][22][23] forming the core of Herzberg-Teller theory. [24][25][26] Indeed, Bersuker has suggested that all chemical processes can be described in this way as a pseudo Jahn-Teller effect.…”
Section: Introductionmentioning
confidence: 99%
“…12 This molecule is an example of how many inorganic molecules delocalize to accommodate mixed valence oxidation states and behave according to molecular orbital states. In particular, this molecule was able to have two channels of relaxation back to the ground state with no fluorescence, and the fastest channel has a strong vibrational coherence.…”
Section: Scientific Summarymentioning
confidence: 99%